Water and Soil Pollution from Rail Transportation: State of Knowledge and Environmental Concerns - Jiri Marsalek; Godecke-Tobias Blecken; Maria Viklander (Water, Air, & Soil Pollution, 2026)
This review synthesizes current knowledge on water and soil pollution attributed to drainage of conventional rail transportation infrastructure (RTI) considered in three categories: (i) tracks and associated structures, (ii) rail yards, and (iii) passenger stations. Pollutants arise from rolling-stock operation, rainwater washoff of infrastructure materials, and maintenance. Resulting runoff can convey metals, polycyclic aromatic hydrocarbons (PAHs), oil and grease, and herbicides. Among metals, zinc is washed off from galvanized steel structures, whereas iron, copper, manganese, and chromium are largely generated by abrasion of rails, wheels, brakes, and overhead wires. PAHs originate in operation of diesel-powered units. Oil and grease loads reflect lubrication of wheel–rail interfaces, switches, and other mechanical components. Herbicides, and particularly glyphosate, remain a focal concern due to potential leaching to groundwater used for drinking water. Experimental evidence and regulatory reviews indicate that risks from glyphosate can be managed with careful applications and exclusion of sensitive zones. Spatially, the highest track-related pollution is typically confined to narrow corridors (< 20 m) running along tracks. Aside from localized exceedances (e.g., herbicides in groundwater immediately beneath tracks, or metals/PAHs in near-track soils), concentrations of pollutants in soils are commonly low. In contrast, rail yards are high-risk industrial sites, with stormwater requiring on-site treatment to prevent releases of petroleum hydrocarbons, metals, and other contaminants to surface water and groundwater. Large urban stations present retrofitting challenges, necessitating drainage upgrades and compliant integration with existing sewer systems. Overall, rails represent an environmentally efficient transport mode, which can be further improved by targeted source controls and site-appropriate stormwater management not interfering with track drainage.

Environmental risk ranking of 20 metal(loid)s in urban runoff: A Swedish nationwide meta-analysis - Ali Beryani; Sarah Lindfors; Franz Kevin Geronimo; Alexandra Müller; Godecke-Tobias Blecken; Lian Lundy; Helene Österlund; Maria Viklander (Journal of Hazardous Materials, 2026)

Design of stormwater bioretention systems for improved volume and peak runoff reduction - Utsav Adhikari; Ico Broekhuizen; Godecke-Tobias Blecken; Maria Viklander (Journal of Hydrology, 2026)

Influence of Salt on Total and Dissolved Metal Treatment in Bioretention: A Field Study - Robert Furén; Maria Viklander; Godecke-Tobias Blecken (Water, Air, & Soil Pollution, 2026)
Urban areas are affected by anthropogenic activities that cause pollutant load on receiving water bodies. Stormwater bioretention are popular and effective in removing pollutants. The main water quality treatment processes are filtration and adsorption in the top layer (0-10 cm) of the filters. So far, few in-field studies have evaluated effects of cold climate and de-icing salt on bioretention for treating metals. Thus, a comprehensive study of total and dissolved metal removal (Cd, Cr, Cu, Ni, Pb and Zn) in a bioretention system for management of road runoff from the European highway E4 was carried out. Three different filter configurations were examined: a sand filter (SF), a vegetated sand filter (BF) and a vegetated sand filter with chalk additive (BFC). The results show a general trend of significant metal removal in all three filters, BFC, BF and SF, both under impact of high (Cl − > 210 mg/l) and low (Cl − ≤ 98.2 mg/l) chloride concentrations. For total metal concentrations, the results show that removal was most efficient in filter BFC, then BF and least efficient in filter SF. For metals such as Cu, Ni and Pb, this may indicate that better removal could be achieved using vegetated filters with chalk additives that affect pH. For dissolved metals, there is a tendence of Cr, Cu, Ni, Pb and Zn removal in filter BFC when lower chloride impact. With higher chlorides concentrations, there tended to be a release of metals from the filters.

Assessment of overall chemical hazard of runoff from eight roofing materials applying effect-based analysis - Snežana Gavrić; Kelsey Flanagan; Heléne Österlund; Godecke-Tobias Blecken; Johan Lundqvist; Maria Viklander (Environmental Pollution, 2026)

Metal treatment in stormwater bioretention systems with high hydraulic conductivity – Designed for more efficient runoff volume capture and cold climates - Robert Furén; Katharina Lange; Ali Beryani; Maria Viklander; Godecke-Tobias Blecken (Journal of Contaminant Hydrology, 2025)

Critical field evaluations of biochar-amended stormwater biofilters for PFAS and other organic micropollutant removals - Ali Beryani; Kelsey Flanagan; Shujie You; Fredrik Forsberg; Maria Viklander; Godecke-Tobias Blecken (Water Research, 2025)

Comparing acute toxicity testing and extensive targeted chemical screening for risk assessment of urban stormwater pond sediments - Kelsey Flanagan; Godecke-Tobias Blecken; Heléne Österlund; Maria Viklander (Journal of Hazardous Materials, 2025)

Microplastics and tyre wear particles in urban runoff from different urban surfaces - Sarah Lindfors; Heléne Österlund; Claudia Lorenz; Alvise Vianello; Kerstin Nordqvist; Kalpana Gopinath; Jeanette Lykkemark; Lian Lundy; Jes Vollertsen; Maria Viklander (Science of The Total Environment, 2025)

Assessing spatial and temporal variability of grass swale infiltration in shallow groundwater conditions - Ivan Mantilla; Tone Merete Muthanna; Jiri Marsalek; Maria Viklander (Journal of Environmental Management, 2025)

Stormwater discharges affect PFAS occurrence, concentrations, and spatial distribution in water and bottom sediment of urban streams - Suna Ekin Kali; Heléne Österlund; Maria Viklander; Godecke-Tobias Blecken (Water Research, 2025)

Green roof runoff reduction of 84 rain events: Comparing Sedum, life strategy-based vegetation, unvegetated and conventional roofs - Joel Lönnqvist; Ico Broekhuizen; Maria Viklander; Godecke Blecken (Journal of Hydrology, 2025)

Building surface materials as potential sources of biocides: Insights from laboratory leaching investigations of different material types - Shadi Kohzadi; Alexandra Müller; Heléne Österlund; Maria Viklander (Chemosphere, 2024)

Impacts of seasonal activities and traffic conditions on the contamination and accumulation of gully pot sediments: Metal(loid)s and organic substances - Haoyu Wei; Lian Lundy; Tone Merete Muthanna; Maria Viklander (Science of The Total Environment, 2024)

Intra-event variations of organic micropollutants in highway runoff and a presedimentation-biofilter treatment facility - Ali Beryani; Kelsey Flanagan; Maria Viklander; Godecke-Tobias Blecken (Journal of Hazardous Materials, 2024)

Retrofit of grass swales with outflow controls for enhancing drainage capacity - Ivan Mantilla; Kelsey Flanagan; Ico Broekhuizen; Tone Merete Muthanna; Jiri Marsalek; Maria Viklander (Journal of Hydrology, 2024)

Microplastics in gully pot sediment in urban areas: Presence, quantities and characteristics - Lisa Öborn; Heléne Österlund; Maria Viklander (Environmental Pollution, 2024)

Traffic-related metals in urban snow cover: A review of the literature data and the feasibility of filling gaps by field data collection - Arya Vijayan; Helene Österlund; Jiri Marsalek; Maria Viklander (Science of The Total Environment, 2024)

Influence of seasonal activities and traffic conditions on the accumulation and particle size distribution of gully pot sediments - Haoyu Wei; Lian Lundy; Tone Merete Muthanna; Maria Viklander (Journal of Environmental Management, 2023)

Impacts of stormwater pipe materials and pipe repairs on stormwater quality: a review - Mehwish Taneez; Heléne Österlund; Lian Lundy; Maria Viklander (Environmental Science and Pollution Research, 2023)
The water quality implications of transferring stormwater through pipes composed of concrete (new and used), polyvinyl chloride (PVC), galvanized corrugated steel (GCS), high-density polyethylene (HDPE), and pipes subjected to cured in place pipe (CIPP) and spray in place pipe (SIPP) trenchless repair technologies on stormwater quality are reviewed. Studies involve either the use of flowing water or an immersion experimental design, with data showing contact with pipe materials can affect stormwater quality parameters including pH, electrical conductivity (EC), and concentrations of minerals, metals, and organic constituents, e.g. styrene. ‘In-transport’ changes in pH (1–3 units), EC (2–3-fold), bicarbonate (3–44-fold), and calcium (2–17-fold) in stormwaters were reported following exposure to concrete pipes. Differences between the use of synthetic and field-collected stormwater were identified, e.g. turbidity levels in field-collected stormwater reduced on passage through all pipe types, compared to synthetic water where levels of turbidity on exposure to concrete and cement-based SIPP increased slightly. Transfer through PVC and HDPE pipes had minimal effects on physicochemical parameters, whereas exposure to galvanized corrugated steel pipes led to increases in EC, Zn, and Pb. Though limited data was available, the use of CIPP repairs and associated waste condensate generated during thermal curing and/or incomplete curing of resins was identified to release organic contaminants of concerns (e.g. styrene, vinylic monomers, dibutyl phthalate (DBP), diethyl phthalate (DEP), and benzaldehyde). The implications of findings for both future research and stakeholders with responsibility for reducing diffuse pollution loads to receiving waters are considered. Graphical Abstract

Performance of a gross pollutant trap-biofilter and sand filter treatment train for the removal of organic micropollutants from highway stormwater (field study) - Ali Beryani; Kelsey Flanagan; Maria Viklander; Godecke-Tobias Blecken (Science of The Total Environment, 2023)

A study of 101 organic substances in gully pot sediments accumulated over a one-year period in Stockholm, Sweden - Haoyu Wei; Kelsey Flanagan; Lian Lundy; Tone Merete Muthanna; Maria Viklander (Science of The Total Environment, 2023)

Accumulation and contamination of gully pot sediments from varied land-use types: metal loads, concentrations and speciation - Snežana Gavrić; Kelsey Flanagan; Haoyu Wei; Heléne Österlund; Lian Lundy; Maria Viklander (Environmental Science and Pollution Research, 2023)
Urban stormwater typically enters sewer networks through gully pots, which allow a primary sedimentation of solids upstream of the piped network. The regular removal and disposal of retained sediment are necessary, costly and can involve environmental risks due to the contamination of sediments with substances from the urban environment such as metals. The concentrations and speciation of Cd, Cr, Cu, Ni, Pb and Zn were analysed in sediments from 26 gully pots located in different land use areas in Stockholm, Sweden. In addition, accumulation rates of both sediment and metal masses were evaluated, providing a basis for optimising maintenance practices and better understanding of impacts of characteristic urban land use types. Metal concentrations varied by at most a factor of eight between samples and were always below Swedish polluted site guidelines for less sensitive land use, with only eight samples exceeding the guideline values for Cu and Zn for sensitive land use. Sequential extraction showed Pb and Zn to be the most mobile metals. Sediment accumulation rates varied from 0.003 to 0.197 kg/m 2 impermeable surface/year. Metal accumulation rates were much more variable than metal concentrations, with a factor of up to 172 between the highest and lowest rates and the highest metal accumulation rates corresponding to the lower range of mass loads in road runoff. Differences in metal concentrations, sediment or metal mass accumulations could not be solely attributed to either traffic or catchment land use. In contrast, traction grit used for winter road maintenance, which has low (but detectable) metal concentrations, is identified as a major component of gully pot sediments, with a combined effect of both moderating metal concentrations and contributing to total mass.

Plant water use related to leaf traits and CSR strategies of 10 common European green roof species - Joel Lönnqvist; Claire Farrell; Dean Schrieke; Maria Viklander; Godecke-Tobias Blecken (Science of The Total Environment, 2023)

Sustainability performance of bioretention systems with various designs - Pär Öhrn Sagrelius; Godecke Blecken; Annelie Hedström; Richard Ashley; Maria Viklander (Journal of Environmental Management, 2023)

Releases of micropollutants from building surface materials into rainwater and snowmelt induced runoff - Alexandra Müller; Heléne Österlund; Kerstin Nordqvist; Jiri Marsalek; Maria Viklander (Chemosphere, 2023)

Modelling the long-term sustainability impacts of coordination policies for urban infrastructure rehabilitation - Youen Pericault; Maria Viklander; Annelie Hedström (Water Research, 2023)

Occurrence and concentrations of organic micropollutants (OMPs) in highway stormwater: a comparative field study in Sweden - Ali Beryani; Kelsey Flanagan; Maria Viklander; Godecke-Tobias Blecken (Environmental Science and Pollution Research, 2023)
This study details the occurrence and concentrations of organic micropollutants (OMPs) in stormwater collected from a highway bridge catchment in Sweden. The prioritized OMPs were bisphenol-A (BPA), eight alkylphenols, sixteen polycyclic aromatic hydrocarbons (PAHs), and four fractions of petroleum hydrocarbons (PHCs), along with other global parameters, namely, total organic carbon (TOC), total suspended solids (TSS), turbidity, and conductivity (EC). A Monte Carlo (MC) simulation was applied to estimate the event mean concentrations ( EMC ) of OMPs based on intra-event subsamples during eight rain events, and analyze the associated uncertainties. Assessing the occurrence of all OMPs in the catchment and comparing the EMC values with corresponding environmental quality standards (EQSs) revealed that BPA, octylphenol (OP), nonylphenol (NP), five carcinogenic and four non-carcinogenic PAHs, and C 16 -C 40 fractions of PHCs can be problematic for freshwater. On the other hand, alkylphenol ethoxylates (OPnEO and NPnEO), six low molecule weight PAHs, and lighter fractions of PHCs (C 10 -C 16 ) do not occur at levels that are expected to pose an environmental risk. Our data analysis revealed that turbidity has a strong correlation with PAHs, PHCs, and TSS; and TOC and EC highly associated with BPA concentrations. Furthermore, the EMC error analysis showed that high uncertainty in OMP data can influence the final interpretation of EMC values. As such, some of the challenges that were experienced in the presented research yielded suggestions for future monitoring programs to obtain more reliable data acquisition and analysis.

Abundance, distribution, and composition of microplastics in the filter media of nine aged stormwater bioretention systems - Katharina Lange; Robert Furén; Helene Österlund; Ryan Winston; R. Andrew Tirpak; Kerstin Nordqvist; Joseph Smith; Jay Dorsey; Maria Viklander; Godecke-Tobias Blecken (Chemosphere, 2023)

Microplastics in urban catchments: Review of sources, pathways, and entry into stormwater - Heléne Österlund; Godecke Blecken; Katharina Lange; Jiri Marsalek; Kalpana Gopinath; Maria Viklander (Science of The Total Environment, 2023)

Polymer-assisted hydraulic dredging for quality control of stormwater pond sediment and reject water – Influence of polymer choice and its preparation - Fredrik Nyström; Inga Herrmann; Annelie Hedström; Maria Viklander (Journal of Water Process Engineering, 2023)

Variability of green infrastructure performance due to climatic regimes across Sweden - Ivan Mantilla; Kelsey Flanagan; Tone Merete Muthanna; Godecke-Tobias Blecken; Maria Viklander (Journal of Environmental Management, 2023)

Correction to: Facilitating maintenance of stormwater ponds: comparison of analytical methods for determination of metal pollution - Snežana Gavrić; Kelsey Flanagan; Heléne Österlund; Godecke‑Tobias Blecken; Maria Viklander (Environmental Science and Pollution Research, 2022)

Facilitating maintenance of stormwater ponds: comparison of analytical methods for determination of metal pollution - Snežana Gavrić; Kelsey Flanagan; Heléne Österlund; Godecke-Tobias Blecken; Maria Viklander (Environmental Science and Pollution Research, 2022)
Stormwater ponds are widely used for controlling runoff quality through the sedimentation of particles and associated pollutants. Their maintenance requires regular removal and disposal of accumulated material. This necessitates an assessment of material hazardousness, including potential hazard due to its contamination by metals. Here we analyze 32 stormwater pond sediment samples from 17 facilities using several chemical analysis methods (total extraction, sequential extraction, diffusive gradients in thin-films DGT, and pore water extraction) in order to consider the complementarity and comparability of the different approaches. No clear relationship was found between analyses that have the potential to measure similar metal fractions (DGT and either fraction 1 of the sequential extraction (adsorbed and exchangeable metals and carbonates) or pore water concentrations). Loss on ignition (LOI) had a significant positive correlation with an indicator of the environmental risk developed in this paper (∑ranks) that incorporates different metals, speciations, and environmental endpoints. Large variations in metal levels were observed between ponds. As clustering was limited between the different analyses, a comprehensive analysis of different parameters is still needed to fully understand metal speciation and bioavailability.

An evaluation of temporal changes in physicochemical properties of gully pot sediments - Haoyu Wei; Tone Merete Muthanna; Lian Lundy; Maria Viklander (Environmental Science and Pollution Research, 2022)
Diffuse pollution is recognised as a major challenge in achieving EU Water Framework Directive compliance, with urban runoff being a key pathway connecting various sources to receiving waters. Gully pots, as one of the ubiquitous urban drainage infrastructures, are placed at the inlets of piped drainage pipe network and actively drain runoff from urban catchment with suspended solids proportionally retained. The physiochemical properties of these retained solids reflect the activities within the catchment during the accumulation period. In this work, seven gully pots in two catchment types (highway and housing) in Luleå, Sweden were fully emptied and sediments analysed for total mass, particle size distribution and selected metal concentrations by six size fractions. The results of this sampling campaign are compared with the results of a 2005 study of the same gully pots to identify changes in the physicochemical properties of sediments over time and examine whether changes identified can be linked to changes in wider catchment management practices. The results highlight the potential impacts of winter road maintenance operations (e.g. up to a 15-fold higher solids loading rate in road catchment gully pots), reaching a normalised solids accumulation rate of 0.176–0.819 kg m 2 year −1 . An increase in tyre and road wear associated with winter road maintenance operations is also understood to contribute to the temporal increase of several metals including Cu, Zn, Co, Cr and V in the < 63-µm solids fraction in the road catchment gully pots. The concentrations of As and Pb decrease in all size fractions in both catchments, with the implementation of unleaded fuels (for Pb in housing catchment only), End-of-Life Vehicle Directive (Directive 2000/53/EC) (for Pb in both catchments), and strengthened industrial emission reduction measures suggested as possible drivers. The high contamination load for Zn, Cu, Cd and Pb in < 63-µm sediments from low-traffic housing catchment also emphasised the necessity of tracing and restricting non-traffic-related metal sources. Further seasonal monitoring of gully pot sediments is recommended to fully follow up the development of metals loading in both catchments.

Temperatures and precipitation affect vegetation dynamics on Scandinavian extensive green roofs - Joel Lönnqvist; Hans Martin Hanslin; Birgitte Gisvold Johannessen; Tone Merete Muthanna; Maria Viklander; Godecke Blecken (International Journal of Biometeorology, 2021)
Standard succulent vegetation mixes developed mostly in temperate climates are being increasingly used on green roofs in different climate zones with uncertain outcome regarding vegetation survival and cover. We investigated vegetation on green roofs at nine temperate, cold, and/or wet locations in Norway and Sweden covering wide ranges of latitude, mean annual temperature, annual precipitation, frequencies of freeze-thaw cycles, and longest annual dry period. The vegetation on the roofs were surveyed in two consecutive years, and weather data were compiled from meteorological databases. At all sites we detected a significant decline in species compared to originally intended (planted/sown) species. Both the survival rate and cover of the intended vegetation were positively related to the mean annual temperature. Contrary to a hypothesis, we found that intended vegetation cover was negatively rather than positively related to mean annual precipitation. Conversely, the unintended (spontaneous) vegetation was favoured by high mean annual precipitation and low mean annual temperature, possibly by enabling it to colonize bare patches and outcompete the intended vegetation. When there is high mortality and variation in cover of the intended vegetation, predicting the strength of ecosystem services the vegetation provides on green roofs is difficult. The results highlight the needs for further investigation on species traits and the local factors driving extinction and colonizations in order to improve survivability and ensure a dense vegetation throughout the successional stages of a green roof.

Estimating Pollution Loads in Snow Removed from a Port Facility: Snow Pile Sampling Strategies - Arya Vijayan; Heléne Österlund; Jiri Marsalek; Maria Viklander (Water, Air, & Soil Pollution, 2021)
Choosing the appropriate sampling strategy is significant while estimating the pollutant loads in a snow pile and assessing environmental impacts of dumping snow into water bodies. This paper compares different snow pile sampling strategies, looking for the most efficient way to estimate the pollutant loads in a snow pile. For this purpose, 177 snow samples were collected from nine snow piles (average pile area − 30 m 2 , height − 2 m) during four sampling occasions at Frihamnen, Ports of Stockholm’s port area. The measured concentrations of TSS, LOI, pH, conductivity, and heavy metals (Zn, Cu, Cd, Cr, Pb, and V) in the collected samples indicated that pollutants are not uniformly distributed in the snow piles. Pollutant loads calculated from different sampling strategies were compared against the load calculated using all samples collected for each pile (best estimate of mass load, BEML). The results/study showed that systematic grid sampling is the best choice when the objective of sampling is to estimate the pollutant loads accurately. Estimating pollutant loads from single snow column samples (collected at a point from the snow pile through the entire depth of the pile) produced up to 400% variation from BEML, whereas samples composed by mixing volume-proportional subsamples from all samples (horizontal composite samples) produced only up to 50% variation. Around nine samples were required to estimate the pollutant loads within 50% deviation from BEML for the studied snow piles. Converting pollutant concentrations in snow to equivalent concentrations in snowmelt and comparing it with available guideline values for receiving water, Zn was identified as the critical pollutant.

Phosphorus and TSS Removal by Stormwater Bioretention: Effects of Temperature, Salt, and a Submerged Zone and Their Interactions - Laila C. Søberg; Ahmed M. Al-Rubaei; Maria Viklander; Godecke-Tobias Blecken (Water, Air, & Soil Pollution, 2020)
To prevent deterioration of receiving water bodies, phosphorus and total suspended solid (TSS) removal from stormwater is commonly targeted, e.g., by bioretention. However, their removal may vary due to ambient conditions and design features. In this study, the effect of a submerged zone with embedded carbon source (SZC), temperature, and (road) salt on phosphorus removal was investigated using a two-level full factorial design. A sand-based filter material was used. Overall, phosphorus and TSS removal percentages were high. Higher temperature (4.6 vs. 17.1 °C) caused higher outflow concentrations, thus lowering removal rates. The presence of salt deteriorated total phosphorus removal, whereas dissolved phosphorus removal was not affected. The impact of the SZC was statistically significant but not regarded to be of practical significance for P removal. In contrast, TSS removal was enhanced by a SZC. The results demonstrated that a relatively simple filter material could provide excellent P removal, avoiding the need for additives suggested in other studies.

Laboratory Melting of Late-Winter Urban Snow Samples: The Magnitude and Dynamics of Releases of Heavy Metals and PAHs - Arya Vijayan; Heléne Österlund; Jiri Marsalek; Maria Viklander (Water, Air, & Soil Pollution, 2019)

Effectiveness of a 19-Year Old Combined Pond-Wetland System in Removing Particulate and Dissolved Pollutants - Ahmed Mohammed Al-Rubaei; Malin Engström; Maria Viklander; Godecke-Tobias Blecken (Wetlands, 2017)

Source-Based Modeling Of Urban Stormwater Quality Response to the Selected Scenarios Combining Future Changes in Climate and Socio-Economic Factors - Matthias Borris; Günther Leonhardt; Jiri Marsalek; Heléne Österlund; Maria Viklander (Environmental Management, 2016)

Comparison of Indicator Bacteria Concentrations Obtained by Automated and Manual Sampling of Urban Storm-Water Runoff - Helen Galfi; Kerstin Nordqvist; Monica Sundelin; Godecke-Tobias Blecken; Jiri Marsalek; Maria Viklander (Water, Air, & Soil Pollution, 2014)

Enhancing the Reliability of Laboratory Phosphorus Filter Tests: Effect of Influent Properties and Interpretation of Effluent Parameters - Inga Herrmann; Amir Jourak; Annelie Hedström; Staffan Lundström; Maria Viklander (Water, Air, & Soil Pollution, 2014)

Stormwater impact on urban waterways in a cold climate: variations in sediment metal concentrations due to untreated snowmelt discharge - Godecke-Tobias Blecken; Ralf Rentz; Charlotte Malmgren; Björn Öhlander; Maria Viklander (Journal of Soils and Sediments, 2012)

Laboratory Study of Stormwater Biofiltration in Low Temperatures: Total and Dissolved Metal Removals and Fates - Godecke-Tobias Blecken; Jiri Marsalek; Maria Viklander (Water, Air, & Soil Pollution, 2011)

Impact of Urban Stormwater on Sediment Quality in an Enclosed Bay of the Lule River, Northern Sweden - Ralf Rentz; Anders Widerlund; Maria Viklander; Björn Öhlander (Water, Air, & Soil Pollution, 2011)

Transport of Total Suspended Solids During Snowmelt – Influence by Road Salt, Temperature and Surface Slope - Camilla Westerlund; Maria Viklander (Water, Air, & Soil Pollution, 2008)

Polycyclic Aromatic Hydrocarbons (PAH) in Water and Sediment from Gully Pots - Kristin Karlsson; Maria Viklander (Water, Air, & Soil Pollution, 2008)

Heavy Metal Removal in Cold Climate Bioretention - Tone M. Muthanna; Maria Viklander; Nina Gjesdahl; Sveinn T. Thorolfsson (Water, Air, & Soil Pollution, 2007)

A Comparison of Snow Quality in Two Swedish Municipalities – Luleå and Sundsvall - Karin Reinosdotter; Maria Viklander (Water, Air, & Soil Pollution, 2005)

Substances in Urban Snow. A comparison of the contamination of snow in different parts of the city of Luleå, Sweden - Maria Viklander (Water, Air, & Soil Pollution, 1999)